Environmental impacts and waste management strategies for hydrometallurgical lithium recovery from lepidolite in the Falchani mining area, Puno, Peru - Contreras, Eliana Mullisaca; Ochoa, Benito Hugo Fernandez; Mayta, Elvis Luis Macedo; Ramirez, Johan Denis Aguilar; Ramirez, Alexander Aguilar (Journal of Degraded and Mining Lands Management, 2026)
Lithium mining is expanding into remote highland areas where site-specific environmental data are scarce. This study assessed the environmental footprint of a hydrometallurgical process to extract lithium carbonate (Li?CO?) from lepidolite ore at the Falchani deposit, Puno, Peru, located above 4,500 m within puna grasslands and bofedal wetlands. The ore was characterised by XRD and ICP-MS, and process conditions were optimised using a 2??² fractional factorial design followed by steepest-ascent experiments. Environmental performance was evaluated through cradle-to-gate LCA, a closed-loop water balance, TCLP classification of solid waste, and stage-by-stage carbon footprint analysis. The optimised process achieved 94.5 ± 0.8% lithium extraction with 99.62 ± 0.04% product purity. Environmental results showed CO? emissions of 5.9 ± 0.3 kg CO? eq/kg Li?CO? (about half that of spodumene processing), freshwater consumption of 38 ± 2 m³/t (with 65% internally recycled), and 18 ± 1 t/t of solid waste meeting TCLP non-hazardous criteria with potential reuse as supplementary cementitious material. These findings indicate that, when environmentally appropriate strategies are designed prior to operation, lithium extraction from Puno pegmatites need not result in the environmental catastrophe some critics anticipate, but can instead support a balance between resource recovery and ecosystem protection in fragile high-altitude environments.